Investigating the effects of solarcure curing method on the compressive strength, microstructure and polymeric reaction of fly ash based geopolymer - Zahid, M. (Elsevier Ltd, 2018)
This paper presents the effects of the specially designed solarcure method on the properties of geopolymer binders. The solarcure method is composed of the box-shaped chamber that works on the principles of trapping solar radiations to regulate the adequate amount of heat and temperature inside the box. Two sets of geopolymer binder mix containing low-calcium fly ash (LCFA) and high-calcium fly ash (HCFA) as a base material was developed. One part of sodium hydroxide (5 M and 10 M) solution mixed with two parts of sodium silicate was used as an alkaline activator. Mortar cubes of 50 mm size were cast and cured in three different regimes; continuous oven (CO) curing, intermittent oven (IO) curing and solarcure (SC) curing were used for the compressive strength test. For constant curing; temperature was maintained at 60 °C 24-h, whereas in intermittent conditions (IO and SC), samples were cured in three cycles; each cycle was composed of 8 h curing then 16 h cooling. For IO curing, the oven temperature was maintained at 60 °C, however for SC curing; the solar-box chamber has achieved maximum inside temperature up to 90 °C for each curing cycle. Specially designed SC technique caused up-to 56 increase in compressive strength as compared to the compressive strength of CO cured samples. SC curing also improved the microstructure properties and geopolymer reaction product. © 2018